Age-related changes in human bone marrow mesenchymal stromal cells: morphology, gene expression profile, immunomodulatory activity and miRNA expression - Massaro, Fulvio; Corrillon, Florent; Stamatopoulos, Basile; Dubois, Nathan; Ruer, Achille; Meuleman, Nathalie; Bron, Dominique; Lagneaux, Laurence (Frontiers in Immunology, 2023)
Introduction: Mesenchymal stromal cells (MSC) are one of the main cellular components of bone marrow (BM) microenvironment. MSC play a key role in tissue regeneration, but they are also capable of immunomodulating activity. With host aging, MSC undergo age-related changes, which alter these functions, contributing to the set-up of “inflammaging”, which is known to be the basis for the development of several diseases of the elderly, including cancer. However, there’s few data investigating this facet of MSC, mainly obtained using murine models or replicative senescence. The aim of this research was to identify morphological, molecular and functional alterations of human bone marrow-derived MSC from young (yBM-MSC) and old (oBM-MSC) healthy donors. Methods: MSC were identified by analysis of cell-surface markers according to the ISCT criteria. To evaluate response to inflammatory status, MSC were incubated for 24h in the presence of IL-1β, IFN-α, IFN-ɣ and TNF-⍺. Macrophages were obtained by differentiation of THP-1 cells through PMA exposure. For M1 polarization experiments, a 24h incubation with LPS and IFN-ɣ was performed. MSC were plated at the bottom of the co-culture transwell system for all the time of cytokine exposure. Gene expression was evaluated by real-time PCR after RNA extraction from BM-MSC or THP-1 culture. Secreted cytokines levels were quantitated through ELISA assays. Results: Aging MSC display changes in size, morphology and granularity. Higher levels of -Gal, reactive oxygen species (ROS), IL-6 and IL-8 and impaired colony-forming and cell cycle progression abilities were found in oBM-MSC. Gene expression profile seems to vary according to subjects’ age and particularly in oBM-MSC seem to be characterized by an impaired immunomodulating activity, with a reduced inhibition of macrophage M1 status. The comparative analysis of microRNA (miRNA) expression in yBM-MSC and oBM-MSC revealed a significant difference for miRNA known to be involved in macrophage polarization and particularly miR-193b-3p expression is strongly increased after co-culture of macrophages with yBM-MSC. Conclusions: There are profound differences in terms of morphology, gene and miRNA expression and immunomodulating properties among yBM-MSC and oBM-MSC, supporting the critical role of aging BM microenvironment on senescence, immune-mediated disorders and cancer pathogenesis.